Serious Game to Training Focus for Children with Attention Deficit Hyperactivity Disorder: “Tanji Adventure to the Diamond Temple” - Raden Bagoes Yudha Rangga Sanjaya; Rahadian Kurniawan; Sri Mulyati; Kukuh Eka Nugraha Chrisna Putra; Restu Rakhmawati (Khazanah Informatika, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) affects the academic performance of youngsters. Children with ADHD struggle to remain focused during learning due to decreased attention and concentration. They are highly active and have trouble remembering teachers' instructions. Attention difficulties, focus disorders, and hyperactivity might hinder learning. This work aims to observe the impact of serious games with a platformer genre and puzzles titled "Tanji Adventure to the Diamond Temple" on the learning activities of kids with ADHD. The goal is to create a fun and engaging learning environment to boost the motivation and focus of those with ADHD. Game development process utilizes iterative prototyping. Each iteration yields a prototype that refines in the next iteration. The game was tested on children with ADHD by examining their behavior before and after playing to evaluate whether new game mechanics were necessary. The review procedure includes observing youngsters and interviewing teachers and involves specialists to evaluate its contents. The study confirms that the concentration of children with ADHD increase after playing the game. The game incorporates elements that help youngsters with ADHD concentrate and increase their attention span